Serotonin—A Driver of Progressive Heart Valve Disease - Waldum, Helge; Wahba, Alexander (Frontiers in Cardiovascular Medicine, 2022)
It is well known that some serotoninergic drugs and neuroendocrine tumours producing serotonin (5-HT) may induce valvular heart disease by stimulation of proliferation of valvular cells via interaction with a 5-HT receptor type 2B. Serotonin could play a role in the pathogenesis of progressive valvular disease for example as a complication of rheumatic fever, in patients with congenital bicuspid aortic valves or in degenerative aortic valve stenosis. The initial inflammation in acute rheumatic fever seems to affect both right and the left-side cardiac valves. Some patients develop chronic right-sided valve disease, particularly in connection with septum defects, though left-sided valves typically are predominantly affected, indicating that high flow velocity and systemic pressure close to the valves may be central in the pathogenesis. Serotonin is transported in granules in blood platelets. Changes in platelet number and concentrations of substances released from platelets in patients with valvular disease indicate that serotonin is released locally by shear stress when passing through an abnormal valve. Accordingly, any functional changes (like bicuspid aortic valves and changes secondary to degeneration) in the valves may progress due to locally released serotonin. Unfortunately, due to serotonin release by sampling and preparation of plasma, local serotonin assessment is not possible. Nevertheless, we suggest that serotonin may play a role in valvular disease in general and that patients may benefit from treatment reducing the effect of serotonin on the heart.